STUDI KUALITATIF TENTANG AKTIVITAS ETNOMATEMATIKA DALAM KEHIDUPAN MASYARAKAT TOLAKI - Sitti Fatimah S Sirate (Faculty of Tarbiyah and Teacher Training Universitas Islam Negeri Alauddin Makassar, 2011)
The article aims at discovering the form of ethno-mathematics activity that exist in Tolaki society at Southeast Sulawesi. This study is a qualitative descriptive research that describe 6 basic activities of Tolaki’s society (1) counting, (2) measuring, (3) deciding location, (4) designing, (5) playing, (6) explaining. The data collection was conducted through observation, interview, and docu-mentation. The data were then analyzed based on logical analysis. The results of the research shows that Tolaki society still maintain the traditional of kalo sara which is part of the six basic activities of Tolaki society well known as ethnomathematics. The writer expected that the Tolaki culture should be maintained as local culture heritage that enrich the national culture.